The effect of ZJXG decoction on the serum levels of GH, CT, PTH and VitD3 in femur fracture rats - xiyiqdu, zhong; Zhang, Hua; Zhu, Hanzhong; Zhang, Jidong; Zhou, Guangzhen; Zhou, Zhen (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
In this paper, we aim to investigate the effects of Zhuang Jin Xu Gu(ZJXG) decoction on the serum levels of growth hormone (GH), calcitonin (CT), parathyroid hormone (PTH) and active vitamin D3 (VitD3) and the femoral fracture healing in rats. Femur fractures were generated in 72 male adult Wistar rats by cutting femur transversely at middle point. ZJXG decoction was administered orally after surgery for 7~28. The healing process was analyzed by gross anatomy and hematoxtlin Eosin (HE) staining in rats. The serum levels of GH and CT were assessed by enzyme linked immunobsorbent assay (ELISA). Gross anatomy indicated that the fibrous callus tissue at the femoral fracture-end increased at 7-28 d following treatment with ZJXG decoction. HE staining showed that the fibrous-granular tissue at the fracture-end changed gradually to fibrous, cartilaginous and osseous callus tissues. ELISA results showed that the GH and CT levels in serum increased significantly 7-14 d following treatment with ZJXG decoction. It is concluded that ZJXG decoction could enhance the fracture healing by reducing the decomposition of GH and CT in femur fracture rats.